Tribological investigation of RBD palm olein in different sliding speeds using pin-on-disk tribotester - Samion, Syahrullail (Sharif University of Technology, 2014)
A tribological investigation, in terms of the coeficient of friction and wear resistance of refined, bleached and deodorized palm olein, was conducted using a pin-on-disk tribotester. Palm oil was selected as a candidate due to its superior tribological properties and its large production, which can lead to the mass production of bio-lubricant. The material of the pin and the disk is Titanium (Ti6Al4V). The experiments were conducted following the ASTM G99. The normal load was 9.8 N and the observation time was 1 hour. The sliding speeds were 0.25 m/s and 1 m/s. In this research, only 5 ml of the test lubricant was applied at the beginning of the experiment to investigate the capability of the lubricant to maintain its function. To make sure the lubricant does not subside due to the centrifugal force from the rotating disk; a groove was crafted on the disk. In this research, the coeficient of friction and wear rate were calculated. From the analyses, the coeficient of friction calculated for palm olein was the lowest for both sliding speed conditions, while the wear rate obtained showed that it was eficient lubricating oil at low speed, with a high wear rate at high speed.